Perlindungan Bagi Perajin Dalam Kerangka Hak Cipta, Desain Industri, dan Indikasi Geografis (Telaah Dari Perspektif Otonomi Daerah) - Pelupessy, Sella Petrix (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the legal instruments of copyright, industrial design and geographical indication (in trademark law) can provide permanent protection for craftsmen and the works of these craftsmen can be regional assets in the perspective of regional autonomy. The research method used is normative and empirical juridical by reviewing and examining the applicable laws and regulations related to legal breakthroughs in Bank secrecy and the reality that occurs in the field. The results of the study revealed that in regulatory references, both in the Copyright Law, the Industrial Law and in the Trademark Law which contain knowledge about Geographical Indications, the term craftsman is not known. According to custom, the term craftsman is used to refer to people whose activities produce handicrafts. These activities include activities that rely solely on or expertise of individuals and/or groups. Article 44 of the Papua Special Autonomy Law mandates the Papua Provincial Government to provide protection for the Intellectual Rights of Indigenous Papuans including craftsmen, all of whom are regional assets.